Secure and Efficient Graph Derivation Representation Approach for Measuring and Distributing Cluster Based Ontology - Suganya, R.; A. Divya (Journal of Advance Research in Mathematics and Statistics (ISSN 2208-2409), 2015)
Secure data transmission for cluster-based measuring and comparing ontologies, where the clusters are formed dynamically and occasionally. We intend two sheltered and resourceful records Transmission(SET) protocols for CWSNs, is SET-IBS and SET-IBOOS, through by means of the IdentityBased digital Signature (IBS) scheme and the Identity-Based Online/Offline digital Signature (IBOOS) scheme in that order. During SET-IBS, protection relies on the rigidity of the DiffieHellman problem in the pairing domain. SET-IBOOS further reduces the computaional overhead for present a graph derivation representation based approach (GDR) for stable semantic quantity, which captures structural semantics of ontologies, which is while its serving relies on the hardness of the discrete logarithm problem. The calculations and simlations are provided to illustrate the efficiency of the new protocols. The domino effect illustrate to, the future protocols have better performance than the existing secure protocols for measuring and comparing ontologies, in terms of security overhead and energy consumption.